Strategic Human Resource Management in Enhancing Employee Loyalty at PT Jembo Cable Company - Endang Hermawan (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to analyze the human resource management (HRM) strategies implemented by PT Jembo Cable Company in enhancing employee loyalty. Employee loyalty is a critical factor in maintaining long-term organizational stability and productivity. The research employed a qualitative descriptive approach with data collected through interviews, observation, and documentation. The findings indicate that the company utilizes several HRM strategies, including career development programs, competitive reward and compensation systems, improvement of the work environment, and continuous training and development. Additionally, open communication between management and employees, as well as participative leadership, play a significant role in fostering employees' emotional attachment to the company. The results suggest that well-structured HRM strategies, oriented toward employee needs, significantly contribute to strengthening employee loyalty. The study recommends that PT Jembo Cable Indonesia continue to enhance responsive and adaptive HRM practices to ensure long-term employee engagement and commitment.